Habitat preference of Neogobius Melanostomus in the Baltic Sea - Willebrand, Sofia (2015)
Round goby, neogobius melanosotmus, is an invasive fish that has spread to the Baltic Sea from the Black sea. The invasion is most likely an effect of transport with ballast water. So far little is known of the impact of round goby in the invaded area, but changes in the food web structure have been observed in the Baltic Sea. In this study the habitat preference of round goby was examined using GAM-modelling and thereafter maps over predicted occurrence were created to see its capacity of further spreading in the Baltic Sea. Monitoring data were gathered from the Baltic Sea, minus the Gulf of Bothnia. Variable data were gathered from rasters via ArcMap, with complementing data for depth measured during monitoring. The result of GAM-modelling shows that the round goby prefers areas close to shipping traffic, with a low percentage in slope, shallow waters, moderately exposed areas and above for wave exposure, with a salinity up to 8 psu. The maps over predicted occurrence shows a probable continued spread along the shallow coasts in the monitored area. The results support earlier knowledge of round goby; however, as the fish spreads further in the Baltic Sea the relationship with other environmental variables may change as it is still competing to find its place in the ecosystem. As the fish has capacity to spread further, more knowledge of how to hinder this inva-sive fish is needed.